2013
DOI: 10.1111/jhn.12038
|View full text |Cite
|
Sign up to set email alerts
|

Salt (sodium chloride) content of retail samples of Nigerian white bread: implications for the daily salt intake of normotensive and hypertensive adults

Abstract: The consumption of some brands of bread by normotensive and hypertensive adults puts them at great risk of exceeding their recommended daily allowance for salt. Thus, there is an urgent need to regulate the amount of salt added to bread. In the interim, compelling bakers to declare the salt content of their products on the packaging could help consumers, especially hypertensive adults, avoid brands with a high salt content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Taking into account recent reports on this topic, the mean Na content of bread was 544 mg/100 g (range: 204-720 mg/100 g) in a study from Nigeria (23) published in 2013, which is approximately 20 % higher than observed in our survey. On the other hand, the mean Na level in bread samples collected in Maputo was similar to that reported in 2010 in Australia (427 mg/100 g) and New Zealand (463 mg/100 g) (15) , and 12 % higher than that described in 2009 in the UK (397 mg/100 g) (24) .…”
Section: Discussioncontrasting
confidence: 45%
“…Taking into account recent reports on this topic, the mean Na content of bread was 544 mg/100 g (range: 204-720 mg/100 g) in a study from Nigeria (23) published in 2013, which is approximately 20 % higher than observed in our survey. On the other hand, the mean Na level in bread samples collected in Maputo was similar to that reported in 2010 in Australia (427 mg/100 g) and New Zealand (463 mg/100 g) (15) , and 12 % higher than that described in 2009 in the UK (397 mg/100 g) (24) .…”
Section: Discussioncontrasting
confidence: 45%
“…Then they were dried in a drying oven at 60 °C for 24 hours and weighed for moisture loss determination. The dried groups of bread from each bakery were ground into powder and homogenized in a kitchen grinder for sodium analysis (Nwanguma & Okorie, 2013).…”
Section: Preparation Of Bread Samplesmentioning
confidence: 99%
“…In Jordan, its prevalence was reported in 2009 to be 32.3% for adults aged 25 years or over (Jaddou et al, 2011). Cardiovascular diseases, hypertension and diabetes are related to westernization that is associated with physical inactivity and high consumption of high salt, simple sugar and fat foods (Nwanguma & Okorie, 2013). In their report on the estimated daily intake of sodium based on Jordanian Household Expenditure and Income Survey (JHEIS, 2010), Takruri and Alkurd (2014), have reported that the daily sodium supply of Jordanians was 6478 mg/capita/day.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations